Age and markers of Leydig cell function, but not of Sertoli cell function predict the success of sperm retrieval in adolescents and adults with Klinefelter's syndrome. (31st July 2015) - Rohayem, J.; Fricke, R.; Czeloth, K.; Mallidis, C.; Wistuba, J.; Krallmann, C.; Zitzmann, M.; Kliesch, S.
Summary Microsurgical testicular sperm extraction (mTESE), combined with intracytoplasmic sperm injection (ICSI) represents a chance for azoospermic men with Klinefelter′s syndrome (KS) to father children. The objective of this study was to identify predictive factors for the success of mTESE from adolescents and adults with KS. The clinical data of 50 late pubertal adolescents (13–19 years) and 85 adult patients (20–61 years) with non‐mosaic KS, who underwent mTESE, were analysed with respect to factors, potentially predictive of active spermatogenesis; specifically a history of cryptorchidism, age, testicular volumes, serum levels of LH, FSH, testosterone (T) and estradiol at the time of surgery. Inhibin B, AMH and INSL3 were additionally analysed in the adolescents. A younger age and a near‐compensated Leydig cell function were associated with higher success of sperm retrieval via mTESE: In adolescents ≥15–19 years, spermatozoa were retrieved in 45%, compared to 31% in adults; in adolescents aged 13–14 years, spermatozoa were collected in only 10%. Adolescents with an LH ≤17.5 U/L, along with a T level ≥7.5 nmol/L had the best success rate (54%), which fell to 44% with higher LH, whereas those with low T (<7.5 nmol/L), irrespective of LH had no sperm retrieval. In adults with T levels above and LH below these thresholds, the success rate was 51%, falling to 19%, if LH was higher. When T was lower than threshold, the rate was 17%. No association between testicular volumes, serum levels of FSH, Inhibin B, AMH, estradiol and mTESE success was found. A history of cryptorchidism was associated with lower retrieval rates. A window of opportunity for an approximate 50% chance to retrieve spermatozoa via mTESE exists for young, late pubertal KS patients between age 15 and young adulthood, when Leydig cell function is at its best. In these cases, referral to a centre of expertise should be considered.